Low-temperature argon and ammonia plasma treatment of poly-3-hydroxybutyrate films: Surface topography and chemistry changes affect fibroblast cells in vitro; European Polymer Journal; Vol. 112 - Surmenev R. A. Roman Anatolievich; Chernozem R. V. Roman Viktorovich; Syromotina D. Dina; Oer K. Kristian; Baumbach T. Tilo; Krauze B. Barbel; Boyandin A. N. Anatoly Nikolaevich; Dvoynina L. M. Lyublyana Mikhaylovna; Volova T. G. Tatjyana Grigorjevna; Surmeneva M. A. Maria Alexandrovna (2019, 2019)
Title screen